2015
DOI: 10.1089/thy.2015.0097
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease Distinctly Affects Relationship Between Selenoprotein P Status and Serum Thyroid Hormone Parameters

Abstract: Impaired renal function is positively correlated with serum concentrations of SePP. In patients undergoing CHD treatment, SePP concentrations were significantly reduced, but the TH profile remained unaffected. These findings indicate an important contribution of kidney function on serum SePP homeostasis, and consequently on Se status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Alteration in selenoprotein homeostasis in CKD patients affecting thyroid hormone profile has been studied by Reinhardt et al . [ 19 ] Selenoprotein P is the major selenium transport protein representing the selenium status in the body. They observed that in patients with chronic renal disease, selenoprotein P had negative correlation with T4 levels, both total and free hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in selenoprotein homeostasis in CKD patients affecting thyroid hormone profile has been studied by Reinhardt et al . [ 19 ] Selenoprotein P is the major selenium transport protein representing the selenium status in the body. They observed that in patients with chronic renal disease, selenoprotein P had negative correlation with T4 levels, both total and free hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion and exclusion criteria: Patients examined in our outpatient clinic for further work-up of presumed kidney damage were evaluated prospectively as previously published to examine the link between selenoprotein P, thyroid hormone, and renal impairment [ 28 ]. Thus, serum samples were drawn from July 2013 to July 2014.…”
Section: Methodsmentioning
confidence: 99%
“…According to Reinhardt and colleagues, in patients with CKD, SeP concentrations increase with impaired renal function (even after correction for age and CRP concentrations), whereas SeP concentrations are significantly lower in dialysis patients [187]. The reasons for the discrepant SeP concentrations among the stages of chronic renal failure are not yet completely defined, though the increased inflammatory status in dialysis patients [188] could play an important pathogenic role.…”
Section: Liver-released Compoundsmentioning
confidence: 99%